Policy Paper : Improvement to Fulfill Needs Health Services for Jember Residents Towards Universal Health Coverage : (Policy Paper : Improvement Pemenuhan Kebutuhan Pelayanan Kesehatan Bagi Penduduk Jember Menuju Universal Health Coverage) - Maya Puspitasari, Febriana (Inovbook Publications, 2024)
This policy paper aims to provide policy recommendations for making improvements in meeting the health service needs of Jember residents towards Universal Health Coverage. So as to encourage improvements in efforts to fulfill health services for Jember residents which are not yet in accordance with the mandate of Law Number 40 of 2004 concerning the National Social Security System and Presidential Instruction Number 1 of 2022 concerning Optimizing the Implementation of the National Health Insurance Program in fulfilling services promotive, preventive, curative and rehabilitative health through Universal Health Coverage. In accordance with presidential instructions and this law, by 2024 Universal Heath Coverage is targeted to reach 98% of the population. Meanwhile, Jember Regency currently has the lowest achievement in East Java Province, namely 71.20%. This condition is very unequal to the condition of the population of Jember Regency, which is the Regency with the highest prevalence of Stunting, Maternal and Infant Mortality in East Java Province. So far, the Jember Regency Government has provided guaranteed health services using a free, curative health service program called J-Pasti Keren. Universal Health Coverage is considered important to improve the community satisfaction index which still gets a